TEACHERS' READINESS TO IMPLEMENT THE MERDEKA CURRICULUM IN LANGUAGE AND LITERACY LEARNING: A MIXED-METHOD STUDY - Helminsyah Helminsyah; Nurul Zikri Filina (Sensei International Journal of Education and Linguistic, 2024)
The Merdeka Curriculum is a new curriculum in Indonesia that gives more flexibility to teachers. In its implementation, teachers have an important role because they are the ones who apply the curriculum in the classroom. This study discusses teachers' readiness to implement the Merdeka Curriculum in language and literacy learning. The study used a mixed-method design. The data were collected through a questionnaire and interviews with language teachers. The data were analyzed descriptively and thematically. The result shows that the readiness of teachers is generally good, but there are still some problems, especially in assessment and differentiated learning. Professional development and collaboration among teachers are needed to improve teachers' readiness. This study is expected to be useful for schools and policy makers.